A highly active non-precious metal catalyst based on Fe–N–C@CNTs for nitroarene reduction. Issue 98 (10th October 2016) - Chen, Jian; Yao, Yi; Zhao, Jiao; Zhao, Yaopeng; Zheng, Yuanyuan; Li, Mingrun; Yang, Qihua
Abstract : An efficient Fe–N–C@CNTs for the hydrogenation of nitroarenes was prepared. ε-Fe3 N is the active site and nitrogen/carbon atoms serve as bridges to transport the dissociated hydrogen atoms via spillover effect. Abstract : Research on transition metal–nitrogen–carbon (M–N–C) materials revealed their potential as catalysts in several important traditional reactions. However, the activity of M–N–C still needs to be further improved and the real active center of M–N–C catalysts is still under debate. In this work, an efficient Fe–N–C@CNTs for the hydrogenation of nitroarenes was prepared by pyrolysis of FeCl3, phenanthroline and CNTs. Fe–N–C supported on CNTs is much more active than that supported on activated carbon, showing the promotion effect of CNTs. The characterization results suggest that the high activity of Fe–N–C is mainly attributed to the formation of ε-Fe3 N, which is the active site for the hydrogenation reaction. Nitrogen/carbon atoms contacted to the active centers could serve as bridges to transport the dissociated hydrogen atoms via spillover effect. The catalytic performance of Fe–N–C was also tested on fixed bed reactor under continuous flow condition for the first time and could smoothly catalyze the reaction for over 300 hours.